Integration of LaMnO3+δ films on platinized silicon substrates for resistive switching applications by PI-MOCVD - Raquel Rodriguez-Lamas; Dolors Pla; Odette Chaix-Pluchery; Benjamin Meunier; Fabrice Wilhelm; Andrei Rogalev; Laetitia Rapenne; Xavier Mescot; Quentin Rafhay; Hervé Roussel; Michel Boudard; Carmen Jiménez; et al. (Beilstein Journal of Nanotechnology, 2019)
The next generation of electronic devices requires faster operation velocity, higher storage capacity and reduction of the power consumption. In this context, resistive switching memory chips emerge as promising candidates for developing new non-volatile memory modules. Manganites have received increasing interest as memristive material as they exhibit a remarkable switching response. Nevertheless, their integration in CMOS-compatible substrates, such as silicon wafers, requires further effort. Here the integration of LaMnO3+δ as memristive material in a metal–insulator–metal structure is presented using a silicon-based substrate and the pulsed injection metal organic chemical vapour deposition technique. We have developed three different growth strategies with which we are able to tune the oxygen content and Mn oxidation state moving from an orthorhombic to a rhombohedral structure for the active LaMnO3+δ material. Furthermore, a good resistive switching response has been obtained for LaMnO3+δ-based devices fabricated using optimized growth strategies.